PENGARUH LOCUS OF CONTROL TERHADAP KEPUASAN KERJA DAN STRESS KERJA SERTA DAMPAKNYA TERHADAP TURNOVER INTENTION (Pada Frontliner PT Bank OCBC NISP Tbk Kantor Cabang Area Jakarta Pusat dan Jakarta Barat) - Amirudin, Amirudin (RJABM (Research Journal of Accounting and Business Management), 2023)
The Influence of Locus of Control on Job Satisfaction and Job Stress and Its Impact on Turnover Intention to Frontliner of PT Bank OCBC NISP Tbk in Central and West Jakarta Area Branch Office".This study aims to determine the effect of Locus of Control on Job Satisfaction and Job Stress and its impact on Turnover Intention to Frontliner of PT Bank OCBC NISP Tbk in Central and West Jakarta Area Branch Office. In this research, the method used is survey quantitative method with associative approach, and to find the data is done by spreading questionnaires to 138 respondents (frontliners).Locus of control has an influence on job satisfaction of 19.6%. Testing the hypothesis obtained t count > t table or (5.764 > 1.977) this is reinforced by the significance probability of 0.000 < 0.05, so H0 is rejected and H1 is accepted, it means that there is positive and significant influence between the locus of control on job satisfaction.Locus of control has an influence on job stress of 9.7%. Testing the hypothesis obtained t count > t table or (3.819 > 1.977) this is reinforced by the significance probability of 0.000 < 0.05, so H0 is rejected and H1 is accepted, it means that there is positive and significant influence between locus of control and job stress.Job satisfaction has influence on turnover intention of 38.2%. Testing the hypothesis obtained t count > t table or (9.170 > 1.977) this is reinforced by the significance probability of 0.000 < 0.05, so H0 is rejected and H1 is accepted, it means that there is positive and significant influence between job satisfaction and turnover intention.Job stress has an influence on turnover intention of 33.1%. Testing the hypothesis obtained t count > t table or (8.208 > 1.977) this is reinforced by the significance probability of 0.000 < 0.05, so H0 is rejected and H1 is accepted meaning that there is positive and significant influence between work stress and turnover intentionJob satisfaction and job stress simultaneously have an influence on turnover intention with contributions influence by 45.5% while the remaining 54.5% influenced by other factors. Statistical hypothesis testing using the F count > F table or (56.393 > 3.06), it is also reinforced with a probability of significance 0.000 < 0.05. Thus H0 is rejected and H1 accepted. This means that there is a positive and significant simultaneous effect between job satisfaction and job stress on turnover intention to Frontliner of PT Bank OCBC NISP Tbk in Central and West Jakarta Area Branch Office.Keywords: Locus of Control, Job Satisfaction, Job Stress and Turnover Intention.